Assessment of the level of awareness of intelligent buildings in Lagos State, Nigeria - Opawole, Akintayo; Olojede, Betty; Oshin, Fumbi; Yusuf, Anthony (Acta Structilia, 2022)
The feasibility of achieving sustainable building development, an eco-friendly environment, and building investment conservation by integrating technological intelligence in buildings is highly viable. Intelligence features are, therefore, increasingly being incorporated in new designs and existing buildings to enhance the useful life, productivity and satisfaction of occupants, and a greener environment. This article evaluates the use of intelligent building systems in Nigeria. Primary data were obtained with the use of structured questionnaires that were self-administered to construction professionals in the private and public sectors in Lagos State. Data collected were analysed using descriptive and inferential statistics. Findings established that 90.24% of the respondents were aware of intelligent building systems, while practitioners who have worked or were working on buildings with intelligent features were limited to 51.2%. Approximately 64.60% of the respondents have used intelligent buildings previously, but only thirteen (13) notable buildings were identified to have employed intelligent building systems to a reasonable extent in the study area. The features of intelligent buildings with top level of awareness were CCTV system; access control and locks (mean = 3.96); alarms and alerts (mean = 3.92); HVAC system (mean = 3.90), and fire alarm system (mean = 3.89). Features with high level of utilisation include lighting system, which was the most utilised feature (mean = 3.57); fire alarm system (mean = 3.48); access control and lock; CCTV system (mean = 3.45), and HVAC system (mean = 3.43). The results showed that most of the features with a high level of awareness were also those with a high level of utilisation. The study established that the level of awareness and utilisation of intelligent building systems in the study area is high, but full adoption of the system is still low.